Relevance of perioperative fluid dynamics in liver transplantation to acute kidney injury and patient outcomes: a cross-sectional survey - Desheng Li; Qinghua Guan; Chuanlin Chen; Bo Sheng; Zhenyu Zhang; Yongfang Hu (Journal of Pharmaceutical Policy and Practice)
Background: Fluid administration is a critical component of perioperative management for liver transplant recipients, and excessive fluid infusion can lead to acute kidney injury (AKI) and poor patient outcomes.Method: We conducted a cross-sectional survey on the fluid intake and output of adult liver transplant recipients over a 7-day period. The patients were divided into AKI and non-AKI groups. Multivariate logistic regression analyses were used to evaluate the association between fluid balance (FB) and AKI. A Kaplan-Meier survival analysis was performed to determine the survival of the recipient survival at 180 days.Results: A total of 210 liver transplant recipients were included. The peak FB occurred on the second day after transplantation, which was higher than on the seventh day (0.3 [IQR, −0.2 to 0.8] L vs. −0.4 [IQR, −1.0 to 0.3] L, p < 0.001). The highest incidence of AKI was observed on the second day after transplantation and the lowest on the seventh day (52.4% vs. 15.4%, p < 0.001). Multivariate analysis showed that a cumulative FB > 1 L within the first 2 days postoperatively was an independent risk factor for AKI on the second day after liver transplantation (LT) (OR = 2.66, 95% CI, 1.31–5.41, p = 0.007). Survival analysis indicated significant differences in 180-day survival rates among patients with different grades of AKI [94.0% (grade 1) vs. 91.4% (grade 2) vs. 77.8% (grade 3), χ2 = 12.93, p < 0.001].Conclusion: There is a significant correlation between post-LT AKI and perioperative FB. Cumulative FB > 1 L in the first 2 days postoperatively is an independent risk factor for AKI on the second day after LT. AKI after LT is associated with a lower 180-day survival rate in patients.